Voice Disorder, Job Stress, and COVID-19 in Teachers: Impacts in Times of Pandemic. - Ferreira do Bonfim, Maria Madalena; Piccolotto Ferreira, Léslie; Mesquita de Medeiros, Adriane; Carolina Constantini, Ana; Vaz Masson, Maria Lúcia (Revista de Investigación e Innovación en Ciencias de la Salud (RIICS), 2024)
Introduction. The conditions of teachers' work during the COVID-19 pandemic affected teachers' lives regarding voice disorder and stress, even in emergency remote classroom situation. Objective. To analyze the relationship between the presence of voice disorder, job stress, and COVID-19 in teachers when in emergency remote classroom teaching situation at the time of the pandemic. Method. This is a primary, exploratory, observational cross-sectional study with the use of survey forwarded online during the period of emergency classes after the arrival of COVID-19 pandemic in Brazil. The teachers answered the sociodemographic questions about the presence of COVID-19 and the following instruments: Condition of Vocal Production-Teacher [Condição de Produção Vocal - Professor (CPV-P)], Screening Index for Voice Disorder (SIVD), and Job Stress Scale (JSS). Results. Of the 118 teachers analyzed, 94.1% were female; the average age was 44 years. The SIVD recorded the presence of voice disorder in 66.9% of the participants. Regarding the JSS, which are the findings related to stress at work in the demand domain, the teachers showed high levels, a fact which presupposes the existence of pressure of psychological nature to perform their work. Conclusion. The teachers self-reported the presence of voice disorder even in remote class situation, on the occasion of COVID-19, which were more common in older teachers. When comparing the presence of voice disorders, coronavirus symptoms, and stress domains in relation to demand, control, and social support, there was no significance. It is hoped that this study will help to reflect on the need to improve teachers' working conditions, strengthening work-related voice disorder actions and guiding actions for vocal care and well-being.